Community-based intervention to dengue prevention: Insights from urban residents in Pune, using the health belief model - Meghana Narendran; Sphurti Chate; Reshma Patil (Clinical Epidemiology and Global Health)
Background: Dengue infection is increasingly recognized as one of the world's emerging infectious diseases. The present study was carried out with the aim of assessing knowledge and health beliefs regarding Dengue fever among community in an urban slum area of Pune. This cross-sectional study was undertaken in an urban slum area of Urban Health Centre, Pashan, which is a field practice area of Department of Community Medicine. Aim & objectives: This study is aimed at understanding the perception towards the Dengue Prevention using the Health Belief Model (HBM) approach, prevention measures adopted, their knowledge, opinion and confidence towards various control measures. Methods: A Cross-Sectional Study using a pre-tested, semi-structured questionnaire was conducted for assessing on knowledge, health beliefs and practice of dengue control. Results: About 26.1 % knew the causes of dengue, 56.2 % had poor knowledge on the severity of dengue. The knowledge on causes (69.9 %), signs and symptoms (77.1 %), treatment (51.2 %) and carriers (86.3 %) of dengue was poor. The knowledge regarding insects breeding spots, potential breeding spots inside (26.1 %) and outside (38.1 %) and prevention was almost poor. The data was collected from the questionnaire, entered and analysed using Statistical Package for Social Sciences (SPSS) version 21.0. Conclusion: Most people living across the community behaved in a similar manner, irrespective of age, education and socio-economic status. Perceptions of the community as explained by Health Belief Model was greatly influenced by their approach to the available health care services and for the subsequent behavioural change.